Photo-induced surface modification to improve the performance of lead sulfide quantum dot solar - Tulsani, Srikanth Reddy; Rath, Arup Kumar (Journal of Colloid and Interface Science, 2018)
The solution-processed quantum dot (QD) solar cell technology has seen significant advancements in recent past to emerge as a potential contender for the next generation photovoltaic technology. In the development of high performance QD solar cell, the surface ligand chemistry has played the important role in controlling the doping type and doping density of QD solids. For instance, lead sulfide (PbS) QDs which is at the forefront of QD solar cell technology, can be made n-type or p-type respectively by using iodine or thiol as the surfactant. The advancements in surface ligand chemistry enable the formation of p-n homojunction of PbS QDs layers to attain high solar cell performances. It is shown here, however, that poor Fermi level alignment of thiol passivated p-type PbS QD hole transport layer with the n-type PbS QD light absorbing layer has rendered the photovoltaic devices from realizing their full potential. Here we develop a control surface oxidation technique using facile ultraviolet ozone treatment to increase the p-doping density in a controlled fashion for the thiol passivated PbS QD layer. This subtle surface modification tunes the Fermi energy level of the hole transport layer to deeper values to facilitate the carrier extraction and voltage generation in photovoltaic devices. In photovoltaic devices, the ultraviolet ozone treatment resulted in the average gain of 18% in the power conversion efficiency with the highest recorded efficiency of 8.98%. (C) 2018 Elsevier Inc. All rights reserved.

Inorganic metal iodide mediated solution phase surface passivation for quantum dot solar cell - Tulsani, Srikanth Reddy; Ganguly, Saptam; Rath, Arup K. (Journal of Materials Science-Materials in Electronics, 2019)
The recent advancements in solution phase surface passivation of quantum dots (QDs) enable the development of production compatible QD ink for their large-area deposition, of a single coating. Surface passivation and colloidal stability of the QDs in polar solvents have been achieved using inorganic-organic hybrid halometallate ligands. The inorganic halometallate anions bind to the unsaturated metal sites of the QD surface, while the organic counter cations provide the colloidal stability and charge balance to the QDs. Organic ligands is a reason for concern though for the stability of the QD solar cells processed from solution-phase ligand exchange. Here, we report a solution-phase ligand exchange strategy using alkali metal halides as a substitution for the organic counterpart to facilitate solution-phase ligand exchange using all-inorganic halometallate ligands. Considering the limited solubility of the alkali halides in organic solvents a two-stage ligand-exchanged process has been commenced to help remove the excess ligands, preserve the electronic purity and allow the formation of highly passivated QD films from solution-phase deposition. A twofold increase in solar cell performance is shown with the help of the modified ligand exchange approach. The solar cell properties are further analysed through detailed characterizations of the QD solar cells.